Vagus nerve stimulation ameliorates cognitive impairment caused by hypoxia - Sharma, Birendra; Jones, Krysten A.; Olsen, Laura K.; Moore, Raquel J.; Curtner, Frances S.; Hatcher-Solis, Candice N. (Frontiers in Behavioral Neuroscience, 2025)
IntroductionHypoxia significantly impairs cognitive function due to the brain’s high demand for oxygen. While emerging evidence suggests that vagus nerve stimulation (VNS) can enhance cognition, its effectiveness in mitigating behavioral and molecular impairments caused by hypoxia remains unknown. This study investigated whether VNS could alleviate hypoxia-induced deficits in cognitive performance and neurotrophin expression in rats.MethodsHealthy male Sprague–Dawley rats were randomly assigned to three groups: sham, hypoxia, and VNS + hypoxia. VNS was delivered during hypoxia (8% oxygen) exposure using 100 μs biphasic pulses at 30 Hz and 0.8 mA. Cognition and performance were assessed by behavioral testing and hippocampal tissue was collected for molecular analysis. NGF and BDNF mRNA levels were measured by quantitative PCR, and protein expression was evaluated by immunohistochemistry.ResultsThe passive avoidance test (PAT) performance was significantly reduced by hypoxia exposure compared to the sham group, and administration of VNS during hypoxia ameliorated this impairment. Hypoxia significantly reduced NGF and BDNF mRNA levels in the hippocampus 24 h post-exposure. VNS restored NGF mRNA to sham levels and partially increased BDNF mRNA. Immunohistochemistry results showed VNS significantly restored NGF protein expression in the hippocampus, while BDNF levels remained unchanged.DiscussionThese findings suggest that VNS may serve as a promising intervention for cognitive impairments induced by hypoxia.